2022
DOI: 10.21203/rs.3.rs-1985746/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Body Mass Index And Inflammation In Depression And Treatment-Resistant Depression: A Mendelian Randomization Study

Abstract: Introduction: Major depressive disorder (MDD) has a significant impact on global burden of disease. Complications in clinical management can occur when response to pharmacological modalities is considered inadequate and symptoms persist (treatment-resistant depression (TRD)). We aim to investigate inflammation, proxied by C-reactive protein (CRP) levels, and body mass index (BMI) as putative causal risk factors for depression and subsequent treatment resistance, leveraging genetic information to avoid confound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…This substantial decrease in adipose tissue could explain our results, given that obesity has been identified as a causal risk factor for most of the outcomes presented in our study. Mendelian randomization studies have confirmed that increased adiposity is causally associated with an increased risk of CVDs, 38 GI diseases, 39,40 depression, 41 cancers, 42,43 and reproductive conditions 44 …”
Section: Discussionmentioning
confidence: 99%
“…This substantial decrease in adipose tissue could explain our results, given that obesity has been identified as a causal risk factor for most of the outcomes presented in our study. Mendelian randomization studies have confirmed that increased adiposity is causally associated with an increased risk of CVDs, 38 GI diseases, 39,40 depression, 41 cancers, 42,43 and reproductive conditions 44 …”
Section: Discussionmentioning
confidence: 99%